Modelo financiero para el control de la productividad del capital de trabajo en las empresas del sector calzado en Cúcuta, Norte de Santander - Jessica Ferley Domínguez-Rangel; Luis Enrique Mendoza; Carlos Alberto Pacheco-Sánchez (Mundo Fesc)
Introduction: Financial control becomes a determining factor for the correct operation of companies, many fail in the first years of work because they do not perform analyses that assess their behavior in accordance with what was projected and executed. Productivity is a determining factor to efficiently measure the resources invested in the working capital of companies. Objective: This article aimed to design a financial model oriented to the development of good control practices in working capital productivity in the footwear sector of Cúcuta. The methodology used is descriptive since it allowed answering the question of what are the relevant variables for working capital productivity, after correlating and generating simulations in the Risk Simulator, identifying the variables that generate the greatest financial impact on footwear companies. In addition, the article presents information from sources that expose applications of the variables necessary for the construction of the model. English: Results: The financial model as a tool for control, monitoring and decision-making in companies in this sector, defines and appropriates relevant variables such as accounts receivable and payable, inventories and income, dependent on the productivity of working capital and the creation of value in companies in the footwear sector in Cúcuta, Colombia. Conclusions: Monitoring accounts receivable is important because a high correlation coefficient (73%) of the CXC with respect to the result of working capital productivity was calculated, this indicates that if a rapid portfolio turnover is not achieved, it will affect productivity and liquidity, decreasing the performance of the organizations.